Artistic Enclaves in the Post-Industrial City : A Case Study of Lawrenceville Pittsburgh - Moss, Geoffrey (Springer International Publishing : Imprint: Springer, 2017)
This SpringerBriefs presents a case study and theoretical analysis of an artistic enclave that emerged within Lawrenceville Pittsburgh. It briefly describes the history of greater Pittsburgh, and Lawrenceville's transition from thriving blue-collar community to depopulated low-income neighborhood to gentrifying site of artistic and creative culture. It draws on multiple methods (e.g., interviews, observations, and survey data) to discuss the advantages and disadvantages associated with being a Pittsburgh artist, and offer a detailed description of the origins and ongoing development of Lawrenceville's artistic enclave. It discusses this enclave in the context of sociological, historical, and interdisciplinary work on urban artistic communities (i.e., bohemian and quasi-bohemian communities), and situates it within the larger urban artistic tradition, and within its contemporary urban context. It maintains that this enclave constitutes a successful (i.e., sustainable) example of an artistic creative class enclave, a heuristic concept that clarifies and amends Richard Florida's brief commentary on contemporary urban artistic life. It concludes by offering policy suggestions for those who wish to promote such enclaves, and a preliminary critical appraisal of their potential impact on society. .
Keywords: Social sciences.; Cultural studies.; Human geography.; elektronické knihy; electronic books